Information and communications security : 17th international conference, ICICS 2015, Beijing, China, December 9-11, 2015, revised selected papers /: 17th international conference, ICICS 2015, Beijing, China, December 9-11, 2015, revised selected papers. (2016) - Unknown
No abstract available